13 : EU green transition as a barrier for socioecological transformations : Deradicalizing transformations, degrowth, decoloniality, and justice in the EU's green politics - Ramcilovic-Suominen, Sabaheta (Routledge, 2025)
This chapter explores the role of state and state policy in transformations by scrutinizing the EU’s Green Deal (EGD) and the EU bioeconomy (EBE), which are landmarks of the EU’s green politics and the green transition (GT). The analysis herein empirically shows that the tensions between the EU’s green policy and the GT on the one hand, and the socioecological transformations on the other originate in the policy design phase already, rather than implementation only. The main motives for policy makers to engage with the language of transformations include (i) climate concerns and the associated public pressure to act on climate change and climate justice and (ii) the EU’s ambition to reinvent itself as a global leader in green technologies and decarbonization, especially in the context of ongoing geopolitical upheaval and wars. These motives are contradictory, as the former requires uprooting and fully transforming the dominant capitalist and growth-oriented model and structures (i.e., a call for transformations), while the latter merely calls for reinventing the current model and capitalist structures as “green”, and in so doing, it emerges as an obstacle for transformations. To balance the tension between the two motives and avoid questioning greening the capitalist growth-oriented model and mentalities, policy makers engage in (i) deradicalization or watering down ideas and agendas associated with transformations, including degrowth and justice and (ii) rationalizing the status quo by elaborating on various barriers for change, many of which concern the EC internal structures and its ways of working and thinking. This in turn deradicalizes and bypasses the politics associated with transformations, degrowth, decoloniality, and justice, which inhibits a shift towards more just, decolonial and post-growth futures, which in turn enables the continuation of injustices, violence, and (neo)coloniality in the EU’s GT and green politics.
Keywords: EU’s Green Deal; EU bioeconomy; green politics; green transition; socioecological transformations